2013
DOI: 10.1097/phm.0b013e31826edcf1
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends in the Management of End-Stage Neuromuscular Respiratory Muscle Failure

Abstract: CNVS and extubation of unweanable patients to CNVS are increasingly being used to prolong life while avoiding invasive interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 70 publications
0
32
0
10
Order By: Relevance
“…Through the late 1920's and into 50's the iron lung was considered to be state of the art, high-tech, life support technology. Indeed medical physician of the time would have learn about such devices as a recommended treatment for respiratory paralysis, used to maintain life for those whose breathing capabilities had been impaired or destroyed by poliomyelitis (1).They were non invasive in the sense that no part of the device penetrated the patient. In truth, it was the patient who was inside the machine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Through the late 1920's and into 50's the iron lung was considered to be state of the art, high-tech, life support technology. Indeed medical physician of the time would have learn about such devices as a recommended treatment for respiratory paralysis, used to maintain life for those whose breathing capabilities had been impaired or destroyed by poliomyelitis (1).They were non invasive in the sense that no part of the device penetrated the patient. In truth, it was the patient who was inside the machine.…”
mentioning
confidence: 99%
“…The first description of ventilator support via mouthpiece was described by Dr.Affeldt of Rancho Los Amigos in 1953 (Figure 2), to assist patients when the iron lung was open for patient care (1,2). He observed that intermittent positive pressure administered by a circuit with a mouthpiece could be used to relieve dyspnea in patients with polio ventilator-dependence when negative pressure ventilation had been interrupted for transfers, nursing or physical therapy (1,2). However, intermittent positive pressure breathing (IPPB) machine became available even earlier than 1951 and a positive pressure blower caller was used to deliver occasional deep breaths as well.…”
mentioning
confidence: 99%
“…Bilevel positive airway pressure machines are considered the best devices to provide NIV, in combination with many kinds of interfaces (oronasal or nasal masks, nasal prongs, and mouthpieces). A special mouthpiece with a lip seal may prevent air leakage in patients whose lips are weak, but nasal prongs can be necessary 26 . Oxygen therapy is not needed and should be avoided in nearly all patients with ALS, since it can exacerbate carbon dioxide retention, resulting in hypercapnic coma or respiratory arrest 23 .…”
Section: Noninvasive Ventilation and Tracheotomymentioning
confidence: 99%
“…Oxygen therapy is not needed and should be avoided in nearly all patients with ALS, since it can exacerbate carbon dioxide retention, resulting in hypercapnic coma or respiratory arrest 23 . A recent consensus recommended the indication of tracheostomy only for patients who cannot maintain a SpO 2 or greater than or equal to 95% despite continuous noninvasive ventilatory support and mechanically assisted cough, a common condition among patients with ALS 26 .…”
Section: Noninvasive Ventilation and Tracheotomymentioning
confidence: 99%
“…As expiratory muscle weakness is a common manifestation of illness, manually or mechanically assisted cough can be useful in selected patients aiming to prevent secretion retention 25 . Moreover, when the inspiratory muscles are significantly compromised, other resources as breath-stacking technique, manual hyperinflation (using a resuscitator bag) and intermittent positive pressure ventilators (volume or pressure controlled modes applied noninvasively by a mouthpiece or mask) can also be used to improve the inspiratory volume prior the forced expiratory maneuver 26 . In severely compromised patients, both inspiratory and expiratory phases can be enhanced by using the mechanically assisted cough, a device specially designed to improve the cough in neuromuscular diseases.…”
Section: Interestingly Halstead and Rossimentioning
confidence: 99%